9‐(4‐Dimethylaminophenyl)benzo[b]quinolizinium: A Near‐Infrared Fluorophore for the Multicolor Analysis of Proteins and Nucleic Acids in Living Cells. Issue 27 (22nd May 2013) - Bortolozzi, Roberta; Ihmels, Heiko; Thomas, Laura; Tian, Maoqun; Viola, Giampietro
<x xml:space="preserve">Abstract</x> All lit up: The title compound operates as a fluorescent light‐up probe that enables the detection of different biologically relevant hosts at different fluorescence maxima. It is demonstrated that this chemosensor also allows the fluorimetric multicolor analysis of different components in living cells (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>